Identification and IVC of spermatogonial stem cells in prepubertal buffaloes - Yu, Xue; Riaz, Hasan; Dong, Ping; Chong, Zhenlu; Luo, Xuan; Liang, Aixin; Yang, Liguo (Theriogenology, 2014)
Development of suitable selective marker for buffalo spermatogonial stem cells (SSCs), optimization of long-term IVC conditions, and their pluripotent retention capacity in buffaloes can be of prime importance in selective genetic modifications of this species. In the present study, we identified CDH1 as a specific marker for buffalo SSCs and revealed that it existed in two protein isoforms (large [135 kDa] and small [90 kDa] subunits) in the buffalo testis; furthermore, immunohistochemical analysis revealed that CDH1 expression was present in spermatogonia but absent in the somatic cells of 4-month-old buffalo testis. After 7 days of enrichment, expression of CDH1 was also detectable in IVC colonies (∼53% enrichment efficiency by Fluorescence-activated cell sorting (FACS)). For long-term culture of SSCs, proliferation studies with different factors showed that combination of 20 ng/mL GDNF, 10 ng/mL FGF2, and 1000 U/mL LIF could significantly promote number of colonies (∼two folds) and proliferation of buffalo SSCs (∼three folds) compared with those of control or single-treatment groups; furthermore, addition of these combination growth factors significantly upregulated the messenger RNA level of spermatogonial-specific and pluripotency-related markers (BCL6B, GFRA1, and POU5F1), whereas downregulated receptor tyrosine kinase (KIT). For confirmation of their stem cell potential, Dolichos biflorus agglutinin–stained cells were identified in the basal membrane of seminiferous tubules of xenotransplanted mice testis. These findings indicate the identification of a new buffalo SSCs marker; furthermore, it may help in establishing long-term culture that would assist in genetic modification of these buffaloes.